Black Youth Matter: An Arts-based and Narrative Study of the Experiences of Black Youth Transitioning out of Child Welfare Care and Their Access to Housing - Davenport, Chelsea (My University, 2020)
Abstract Background: There has been minimal research conducted on the unique experiences of Black youth who transition out of the child welfare system, and as well as the factors that contribute to their success or failure to accessing housing. Purpose: The purpose of study is to explore the needs and experiences of Black youth using Critical Race theory, BlackCrit and Social Capital theory to better understand their experience accessing safe, affordable housing within the Greater Toronto Area after transitioning out of child welfare. Methods: Five Black youth were recruited using site sampling and snow-ball sampling to participate in an arts-based and narrative study. The data was then analyzed in a constant comparative method. Findings: The findings from this study suggest the following things: The emotional roller coaster of being in care, the importance of community and sense of family, youth voices in decision-making process, unpreparedness for independent living, the unawareness of housing options, youth definition of good housing, more resources are needed prior to departure of child welfare. Implications and Recommendations for Change: In light of the findings in this study, a number of recommendations are proposed for improving outcomes for Black youth leaving care and their access to housing. Below is a summary of recommendations: A. To focus on building and providing genuine relationships through a caring adult and permanency for Black youth in care B. Centralize and value the voices of Black youth in care throughout their post-care planning, policy development and research C. To address and respond to the unique experiences that Black youth with disabilities face within the housing market when preparing them for independence outside of the CWS D. To apply a Housing first Youth approach It is my hope that this information will be used to support policy changes and program development in child welfare and the rental housing market that can result in more successful outcomes for Black youth.
Keywords: adolescent youth leaving care; Post care options; ethnic minority youth transitioning from care; ethnic youth transition and homelessness; youth transition and marginalization; Black youth leaving the CWS; photovoice; African Canadian youth aging out of care and child welfare; BlackCrit